(untitled) (Nexus International Journal of Science and Education, 2024)
The study was conducted to understand and describe the experiences of teachers in Calinan District redefining their instructional strategies given new learning modalities in the new face-to-face classes. A qualitative research design was used, and assumptions regarding selecting participants and ethics in collecting, analyzing, and interpreting data were considered. Respondents were the elementary teachers purposely selected through referrals. Given their undertakings as novice teachers, they used facilitating questions to draw narratives on their experiences, challenges, coping mechanisms, and further learning insights. Findings revealed that experiences of teachers found to have been challenged with pre-teaching vocabulary, providing sentence frames and starters, and using visual aids and vocabulary. Coping mechanisms are flexible and adaptable, becoming technologically literate and integrative and watching self-care and well-being. Educational insights were found to support continuous professional development, positive school culture, and the use of technology and literacy. Future direction may provide an opportunity to explore the long-term effects of the coping mechanisms employed by teachers and the effectiveness of the strategies employed in addressing the challenges encountered. Future research can also focus on developing innovative approaches to support teachers in coping with the demands of the new face-to-face